Designing a Website-Based Information System with the Prototyping Method for Stratification of Usaha Kesehatan Sekolah in Boyolali District - Umaroh, Ayu Khoirotul; Priyawati, Diah; Susanto, Edi; Arodah, Nike Indah; Sujarwo, Anton (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background: The Indonesian government promotes health at the school level by developing School Health Program or Usaha Kesehatan Sekolah (UKS). However, the evaluation and monitoring of these program are still weak. The assessment of the UKS indicators then becomes the basis for the UKS classification, which is referred to as stratification. Therefore, this study aimed to design a UKS stratification system by utilizing school self-assessments. Method: This study used a research and development with the development of the SDLC-prototype model. This research was conducted at three elementary schools, two junior high schools, and two community health centers in Boyolali District. The model was developed in three stages: defining system requirements, designing the systems, and developing prototypes. Findings: The study found that the informants felt it necessary to have the system and were increasingly assisted in developing the UKS with the system. The system was created using the MySQL database. The UKS stratification system is named Sistauks.net, which can be operated from a mobile phone or laptop. Sistauks.net consists of school data entries, the UKS administration and infrastructure, health education, health service indicators, and indicators for fostering a healthy school environment. Conclusion: Sistauks.net can automatically identify the right UKS stratification for elementary or junior high schools by completing an assessment in the system. In addition, health center staff that holds the UKS program can also see the results of the submissions from their partner schools. Using the system will make analysis results faster and more accurate.